Expectativas de la familia indígena frente a la educación : análisis de caso en la comunidad Pitana Bajo, parroquia Cangahua. - Tipanluisa Quinatoa, Manuel Mesias (2017)
The purpose of this research is to know the expectations of the indigenous family against education in the Pitaná Bajo community, Cangahua parish, Cayambe canton, to determine how education benefits indigenous families today, it is important to mention that According to the problematic raised was to know the difficulties that the indigenous communities suffer with respect to education, lack of economic resources, unemployment, the accelerated increase of the technology and the geographical location in which they are far from the urban center, For easier access to goods and services including quality education as determined by cities. So knowing the expectations will allow them to know that they want to achieve dares of education towards the hole for their children. We seek to know how the expectations of parents and the educational community, ratify the need to continue policies and strategies in line with their culture and reality, as well as to guarantee access to vocational training that will enable us to overcome poverty community. In the first section we approach the concept of expectation about education that fits the case study, with historical support. The following section presents the results of the research carried out in the Pitaná Bajo community on: the expectations of indigenous families in relation to education. The third section presents the analysis of the results in relation to our concepts.